Optimization of Stope Structural Parameters Based on Mathews Stability Graph Probability Model - Long Zhang; Jian-hua Hu; Xue-liang Wang; Lei Zhao (Advances in Civil Engineering)
Strip mining with subsequent filling is one of the main mining methods for gently inclined thin ore bodies. The production process of excavating alternate strips is beneficial to the safety of mining. Reasonable stope structural parameters are key to achieving safe and efficient mining. The Tiaoshuihe phosphate mine of Sanning Mining is taken as an example in this study. Based on precision finite element modeling and simulation, a reasonable width range and the interval value of the strip are determined. A reliable and efficient strip width is calculated by using the probability model of the improved Mathews stability graph method. The results show the following. Firstly, under the geological conditions and backfill environment of the Tiaoshuihe phosphate mine, the reasonable and safe strip width interval is 7–9 m. Secondly, the probabilities of open stope stability with strip widths of 7, 8, and 9 m are 88.55%, 86.76%, and 84.94%, respectively. The reasonable probabilities of stope stability with strip widths of 7 and 8 m are higher than 85%. Thirdly, combining this with the drilling equipment operation parameters, it is suggested that the best strip width is 7 m without increasing the strength of the backfill.